2015
DOI: 10.1159/000430172
|View full text |Cite
|
Sign up to set email alerts
|

The Down-Regulation of MicroRNA-497 Contributes to Cell Growth and Cisplatin Resistance Through PI3K/Akt Pathway in Osteosarcoma

Abstract: Background: Down-expression of microRNA-497 (miR-497) was often found in malignancies. The purposes of this study were to determine the expression of miR-497 in human osteosarcoma and to establish the association between miR-497 expression with cell survival and the sensitivity to cisplatin in human osteosarcoma cells. Methods: The effects of ectopic miR-497 expression on the cell survival and cisplatin sensitivity in osteosarcoma cells were measured by the Cell Counting Kit-8 (CCK-8) assay. Quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Past studies have demonstrated the regulation effects of miRNAs on protein expression. MiRNAs combine with 3′-untranslated region (3′-UTR) of the mRNA of certain protein thus regulating the intracellular protein expression [20-24]. Many biological events including development of a tumor would be regulated by miRNAs [20-24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have demonstrated the regulation effects of miRNAs on protein expression. MiRNAs combine with 3′-untranslated region (3′-UTR) of the mRNA of certain protein thus regulating the intracellular protein expression [20-24]. Many biological events including development of a tumor would be regulated by miRNAs [20-24].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs combine with 3′-untranslated region (3′-UTR) of the mRNA of certain protein thus regulating the intracellular protein expression [20-24]. Many biological events including development of a tumor would be regulated by miRNAs [20-24]. In addition, the aberrant expression of miRNAs would contribute to OS initiation, progression, outgrowth, metastases, as well as resistance to chemotherapy [20-24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has shown that miRNAs play a vital role in drug resistance [7,8], which leads to treatment failure in cancer. For example, miR-497 sensitizes osteosarcoma cells to cisplatin (DDP), in part via the PI3K/Akt pathway [9]. MiR-17 and miR-92 families play a role in DDP resistance and can be considered novel biomarkers for platinum-based chemotherapy in NSCLC [10].…”
Section: Introductionmentioning
confidence: 99%
“…[7-9]. A recent microarray profiling study identified 177 miRNAs differentially expressed in osteosarcoma cell lines compared with normal bone, and the involvement of selected miRNAs was confirmed in clinical samples [10-12]. miR-661 was suggested to be involved in cancer, although its function is controversial.…”
Section: Introductionmentioning
confidence: 99%